Therapeutic efficacy of low‐dose (25 mg) mirabegron therapy for patients with mild to moderate overactive bladder symptoms due to central nervous system diseases. Issue 2 (30th January 2018) - Chen, Sheng‐Fu; Kuo, Hann‐Chorng
Abstract : Objective: The incidence of overactive bladder (OAB) increases with age, especially in patients with central nervous system (CNS) disorders such as cerebrovascular accident (CVA) and Parkinson's disease (PD). Mirabegron is a novel medication for the treatment of OAB. The present study investigated the therapeutic effect of mirabegron on OAB patients with CNS diseases. Methods: Patients with CVA, PD, dementia, and OAB symptoms were consecutively enrolled in the study group, and mirabegron 25 mg q.d. was prescribed. Clinical effects, evaluated using the Overactive Bladder Symptom Score (OABSS), Urinary Sensation Scale (USS), International Prostate Symptom Score (IPSS), and Patient Perception of Bladder Condition (PPBC), as well as urodynamic parameters and adverse events were assessed at baseline and 4 and 12 weeks after treatment. Results: In all, 44 patients (mean [± SD] age 77.7 ± 9.49 years) with OAB due to CVA (n = 27), PD (n = 6), and dementia (n = 11) were included in the present prospective study. Mirabegron resulted in significant improvements in symptom scores on the OABSS ( P = .02), USS ( P = .009), total IPSS ( P = .002), Storage and Voiding domains of the IPSS ( P = .001 and .017, respectively), and PPBC ( P = .001). No significant changes were noted in post‐void residual, maximum flow rate, and voided volume after treatment. Only 5 patients dropped out due to poor therapeutic efficacy and shifted to antimuscarinics. Three patients complained of adverse effects, including dizziness and dysuria. No patient complained of urine retention or constipation. Conclusion: Mirabegron 25 mg once daily effectively decreased urgency symptoms in elderly OAB patients with CNS lesions after the 12‐week treatment period. The adverse events were mild and only noted in a few cases.